The Archaeology of Fazzan, Volume 3 Excavations of C. M. Daniels - Mattingly, David J. (Society for Libyan Studies, 2010)
The Archaeology of Fazzan is a major series of reports on the archaeology and history of Libya's south-west desert region. This volume contains reports and analysis on a series of excavations carried out between 1958 and 1977 by the British archaeologist Charles Daniels, lavishly illustrated by site plans and numerous colour photographs - particularly of the rich artefact assemblages recovered. The publication will be high profile and a significant landmark in work seeking to record information about Libya's long-term Saharan heritage. It will be an indispensable reference work to the nature of the Libya's Saharan archaeology. The work will be of major value to the Libyan antiquities service and contracted archaeologists in concert with foreign oil companies, the NOC and the GMMR, and other similar major schemes. The key element of the story of Fazzan is the existence here of an early Libyan civilisation, the Garamantes, and the publication of the Archaeology of Fazzan volumes is putting in the public domain a rich dossier of information about their antecedents and descendants in this desert environment. This was a singularly important moment in Libya's cultural history, with resonances also in Sub-Saharan Africa. There is great interest in the published volumes from specialists in Saharan, Sub-Saharan and Mediterranean archaeologists and historians as for the first time we can see in detail the effect of early Trans-Saharan links.